2019
DOI: 10.1177/0961203319887229
|View full text |Cite
|
Sign up to set email alerts
|

Hemoptysis and a cardiac murmur: is it primary or secondary antiphospholipid syndrome?

Abstract: Endocarditis is most frequently infective in origin, and thus, when a patient presents with a clinical picture suggestive of endocarditis, an extensive work up aimed at finding the infectious agent is warranted. Among systemic lupus erythematosus (SLE) patients, cardiovascular disease is prevalent in more than 50% of patients including valvular disease and non-infective endocarditis, known as Libman–Sacks (LS) endocarditis. The prevalence of LS syndrome among SLE patients with secondary antiphospholipid syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Unfortunately, our study does not reach the same conclusion. Other studies have showed that patients with SAPS are more likely to develop more severe diffuse alveolar hemorrhage (DAH) and non-infectious endocarditis, known as Libman-Sacks (LS) endocarditis, especially in APS secondary to SLE (47,48). Only one other study reported differences in immune function between PAPS and SAPS patients, but the lower serum C3 and C4 levels in PAPS patients (9) were inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, our study does not reach the same conclusion. Other studies have showed that patients with SAPS are more likely to develop more severe diffuse alveolar hemorrhage (DAH) and non-infectious endocarditis, known as Libman-Sacks (LS) endocarditis, especially in APS secondary to SLE (47,48). Only one other study reported differences in immune function between PAPS and SAPS patients, but the lower serum C3 and C4 levels in PAPS patients (9) were inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…It is reported that antiphospholipid antibodies may be present in 54% of patients while only 10% of SLE patients develops APS (3). Moreover, primary APS patients are also descried to have LS valve lesions (4). In addition, thrombocytopenia, one of the common manifestations of SLE, is considered to be associated with the higher incidence of valve abnormalities in patients with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that antiphospholipid antibodies may be present in 54% of patients, while only 10% of SLE patients develop APS (3). Moreover, LS valve lesions have been described in primary APS patients (4). In addition, thrombocytopenia, one of the common manifestations of SLE, is considered to be associated with a higher incidence of valve abnormalities in patients with SLE.…”
Section: Introductionmentioning
confidence: 99%